2019
DOI: 10.1371/journal.pone.0223329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical manifestations, health risks, and quality of life among women with polycystic ovary syndrome

Abstract: This study aimed to evaluate the clinical manifestations and health risks associated with polycystic ovary syndrome (PCOS) and its impact on quality of life (QOL) in Pakistan. A detailed cross-sectional study was conducted on PCOS among women of reproductive age visiting the gynecology and obstetrics and endocrinology departments at primary and tertiary care hospitals located in Abbottabad, Kohat, and Islamabad. In total, 440 patients meeting the inclusion criteria were included. A checklist was specifically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
4
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 36 publications
4
75
4
9
Order By: Relevance
“…One cross-sectional showed that 87 % of PCOS patients with hirsutism had poor QOL; they found that those patients with hirsutism had lower QOL than non-hirsute patients. In this study, most patients had not been used any treatment for hirsutism [6]. Two studies showed a signi cant improvement of the hirsutism aspect after 6 months [14] and 12 months [12] of OC therapy; however, these studies did not compare different OCs regarding their progestin component.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…One cross-sectional showed that 87 % of PCOS patients with hirsutism had poor QOL; they found that those patients with hirsutism had lower QOL than non-hirsute patients. In this study, most patients had not been used any treatment for hirsutism [6]. Two studies showed a signi cant improvement of the hirsutism aspect after 6 months [14] and 12 months [12] of OC therapy; however, these studies did not compare different OCs regarding their progestin component.…”
Section: Discussionmentioning
confidence: 82%
“…They observed that PCOS was managed in only 74.6 % of these patients with depression. In addition, poor QOL was observed in 87.8 % of these patients, whereas only 9.2 % of PCOS patients who received treatment had poor QOL [6], ndings suggesting the need for managing psychological disorders in women with PCOS. According to the American Association of Clinical Endocrinologists, the American College of Endocrinology, and the Androgen Excess and PCOS Society recommendations for evaluation and treatment of PCOS patients, all women with PCOS should be screened for anxiety and depressive disorders during the initial examination and its use at further stages of treatment and after it [42].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations